Studies on Polymer Supported Copper Complexes: A Comparison of EPR Data. - CHACKO, SHEELA; MATHEW, TESSYMOL; PADMANABHAN, M.; KURIAKOSE, SUNNY (Asian Journal of Chemistry, 2010)
2 percent divinyl benzene (DVB) crosslinked polystyrene support was synthesized by suspension copolymerization technique and functionalized to get chloromethyl function. A series of ligands were anchored on to the polymer support by suitable chemical modifications. The ligands selected were Schiff bases, ethylene diamine and dithiocarbamates. The polymeric ligands were complexed with copper by simple chemical reactions. SS, NN, NO and OO donor sites form copper complexes with differing spectral and magnetic propeities. The complexes were characterized by IR, UV-Vis and EPR studies. By varying copper environment, EPR parameters were measured and analyzed systematically. The structure, geometry dnd chemical properties of these complexes were studied from the spectral results.